Finishing System for Oil Palm Empty Fruit Bunch (EFB) Medium Density Fiberboard - Yusop, Ahmad (2001)
This study evaluates the surface properties of finished oil palm Empty Fruit Bunch (EFB) Medium Density Fiberboard (MDF) coated with different finishing system. Two types of lacquer i. e. , Acid Catalyst (AC) and Nitrocellulose (NC), were used in this work. The 20 mm thick EFB MDFs were cut to 150 x 100 mm size. The boards were coated with five different treatments: (1) a wash coat, a sealer, and a top coat, (2) a sealer and two top coats, (3) two sealers and a top coat, (4) a wash coat, two sealers, and a top coat, and (5) a wash coat, two sealers, and two top coats. The coated boards were assessed for impact, adhesion and gloss (at 20°, 60°, and 85°), according to British Standard BS 3962 Part 6 (1975) and ASTM D523-67 (1967). The result shows that MDF coated with AC lacquer has higher finish uptake (4.31 g/m2) and good impact rating (3) compare to that of NC lacquer (3. 01 g/m2 and 3 respectively). NC gives better gloss compared to AC lacquer. No significant difference was detected between AC and NC lacquers in terms of adhesion. The results also indicate that all the treatments used in this study have no significant influence on both the amount of finish uptake and impact resistance of the coated MDF. Among the treatments used, that with two sealers and a top coat (treatment 3) gives good adhesion. However, surface gloss was significantly affected by the surface treatment. Highest gloss was obtained by either applying a sealer and two top coats (treatment 2) or by applying a layer of wash coat, two sealers, and two top coats (treatments 5). The best finishing system for EFB MDF is given by NC with a sealer and two top coats (treatment 2).